A Case of Renal Pelvic Cancer Complicated by Horseshoe Kidney Treated with RoboSurgeon Gasless Single-Port Retroperitoneoscopic Nephroureterectomy. (18th September 2018) - Suzuki, Hiroaki; Takemura, Kosuke; Sakamoto, Kazumasa; Kataoka, Madoka; Ito, Masaya; Nakanishi, Yasukazu; Tobisu, Ken-ichi; Koga, Fumitaka
Abstract : A 78-year-old man who had a horseshoe kidney (HSK) visited us because of gross hematuria and suspicious urine cytology. CT and MRI revealed a right renal pelvic tumor of 28 mm in diameter. He underwent gasless single-port retroperitoneoscopic nephroureterectomy with division of the isthmus via the right pararectal small incision using the RoboSurgeon system. Pathological diagnosis was invasive urothelial carcinoma, grade 3, pT3, pN0, LVI0, RM0. He was discharged from hospital on the 6th postoperative day without any perioperative complication. He has no evidence of disease clinically and radiologically 19 months after the operation. Only a few cases of upper tract urothelial carcinoma complicated by HSK treated with minimally invasive surgery have been reported in English literature. This is the first case successfully managed with RoboSurgeon gasless single-port retroperitoneoscopic nephroureterectomy.